Suicides au travail : un drame de la conscience professionnelle ? - Yves Clot (Activités)
The article proposes a working hypothesis on suicides in the workplace. Based on Vygotsky’s work on activity theory and on G. Canguilhem’s analysis of consciousness, it discusses the results of the sociology of suicide. It outlines the ongoing debates in work psychopathology. It develops the idea that suicides at work are dramas of work ethics and professionalism. The confusion between collective consciousness and self-consciousness must be studied to achieve a better understanding of the relationships between the individual and the organization of work which are at the heart of the problem.